New research could help farmers identify land for groundwater recharging. Issue 2 (24th May 2016) - Cushman, Will
Abstract : California is entering its fifth year of unprecedented drought. Researchers hope a new online tool will assist growers and landowners in replenishing badly needed groundwater. Earn 0.5 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/761 .